The Effect of Work Motivation and Rewards on Investigators Criminal Performance at Polres Konawe - Sugeng, Umar Rumendan (International Journal of Management and Education in Human Development, 2021)
This study aims to analyze to know and explain empirically the influence of the provision of work motivation and reward on the performance of investigators unit Reskrim Polres Konawe either partially or simultaneously. The population in this research are all Konawe Police Criminal Investigators with 46 persons who are members of Resort Police of Konawe District who have reskrim function or investigator. The technique of determining the sample using statistical methods or saturated samples in which all of the population will be sampled. The data analysis method used is multiple linear regression analysis. The result of the research shows that the motivation of work and reward simultaneously have positive and significant influence on performance of investigator of reskrim at Konawe Resort Police, while the giving of motivation to investigator in this research have positive but not significant influence to the performance, then for reward for investigator work have positive influence and significant to the performance of Investigators on the function of Konawe Polres Reskrim.